Matrigel and Activin A promote cell-cell contact and anti-apoptotic activity in cultured human retinal pigment epithelium cells. (June 2016) - Guo, Xiaoling; Zhu, Deliang; Lian, Ruiling; Han, Yuting; Guo, Yonglong; Li, Zhijie; Tang, Shibo; Chen, Jiansu
Abstract: Age-related macular degeneration (AMD) is a leading cause of blindness among the aging population. Currently, replacement of diseased retinal pigment epithelium (RPE) cells with transplanted healthy RPE cells could be a feasible approach for AMD therapy. However, maintaining cell-cell contact and good viability of RPE cells cultured in vitro is difficult and fundamentally determines the success of RPE cell transplantation. This study was conducted to examine the role of Matrigel and Activin A (MA) in regulating cell-cell contact and anti-apoptotic activity in human RPE (hRPE) cells, as assessed by atomic force microscopy (AFM), scanning electron microscope (SEM), immunofluorescence staining, quantitative polymerase chain reaction (qPCR) analysis, Annexin V/propidium iodide (PI) analysis, mitochondrial membrane potential (△Ψ m) assays, intracellular reactive oxygen species (ROS) assays and Western blotting. hRPE cells cultured in vitro could maintain their epithelioid morphology after MA treatment over at least 4 passages. The contact of N-cadherin to the lateral cell border was promoted in hRPE cells at P2 by MA. MA treatment also enhanced the expression of tight junction-associated genes and proteins, such as Claudin-1, Claudin-3, Occludin and ZO-1, as well as polarized ZO-1 protein distribution and barrier function, in cultured hRPE cells. Moreover, MA treatment decreased apoptotic cells, ROS and Bax and increased △Ψ m and Bcl2 in hRPE cells under serum withdrawal-induced apoptosis. In addition, MA treatment elevated the protein expression levels of β-catenin and its target proteins, including Cyclin D1, c-Myc and Survivin, as well as the gene expression levels of ZO-1, β-catenin, Survivin and TCF-4, all of which could be down-regulated by the Wnt/β-catenin pathway inhibitor XAV-939. Taken together, MA treatment could effectively promote cell-cell contact and anti-apoptotic activity in hRPE cells, partly involving the Wnt/β-catenin pathway. This study will benefit the understanding of hRPE cells and future cell therapy. Highlights: The anti-apoptotic activity in hRPE cells was enhanced with Matrigel and Activin A (MA) treatment. At the treatment of MA, the tight junctions (TJs) of hRPE cells were maintained very well at least for 4 passages. MA treatment could promote TJs and anti-apoptotic activity in hRPE cells, partly involving the Wnt/β-catenin pathway.